ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2016 - Nico Anangsyah; Desta Rizky Kusuma (Universitas Ahmad Dahlan, 2018)
This study aims to determine the analysis of factors affect the capital structure of registered textile and garment companies on the Indonesia Stock Exchange (IDX) for the 2014-2016 period. Variables in this study namely Profitability (ROA), Asset Structure (SA), Sales Growth (PP) and Company Size (SIZE) and Capital Structure (DER). The population in this study is the Textile and Garment company listed on the Indonesia Stock Exchange (IDX) as many as 17 companies later 15 companies were sampled using a purposive technique sampling. The analysis technique used is panel data regression analysis with comparison of t-statistics with t-tables. The results of this study indicate that profitability (ROA) is not positive effect on Capital Structure (DER), t-statistic of 1.386407. Asset Structure (SA) has no positive effect on Capital Structure (DER), statistic equal to 0.296574. Sales Growth (PP) influences positive for Capital Structure (DER), the statistic is 1.873566. Size The company (SIZE) does not have a positive effect on the Capital Structure (DER), statistic at 0.570955.